Menguatnya Politik Identitas Di Ranah Lokal - HABODDIN, MUHTAR (Universitas Muhammadiyah Yogyakarta, 2012)
The strengthening of identity politics in the local domains happens together with politicaldecentralization. Post-enactment of Law 22/1999, identity politics movements is more clearly . In fact,Many actors both local and national politics are consciously using this issue in the power-sharing.This research use literature review as method in analysis. Identity politics In Riau, CentralKalimantan, West Kalimantan and Irian Jaya, which is become the focus of this study, are show howstrength this issue. This issue used by political actors when dealing with other political entities.